Control of Herbaspirillum seropedicae NifA Activity by Ammonium Ions and Oxygen - Souza, E. M. (American Society for Microbiology, 1999)
The activity of a truncated form of Herbaspirillum seropedicae NifA in different genetic backgrounds showed that its regulatory domain is involved in nitrogen control but not in O(2) sensitivity or Fe dependence. The model for nitrogen control involving PII could thus apply to the proteobacteria at large. NifA may have a role in controlling ADP-ribosylation of nitrogenase in Azospirillum brasilense.